2016
DOI: 10.4236/ijmpcero.2016.54031
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Estimating Patient-Specific Dose Verification Results Directly from Linear Accelerator Log Files in Volumetric Modulated Arc Therapy

Abstract: The feasibility of estimating patient-specific dose verification results directly from linear accelerator (linac) log files has been investigated for prostate cancer patients who undergo volumetric modulated arc therapy (VMAT). Twenty-six patients who underwent VMAT in our facility were consecutively selected. VMAT plans were created using Monaco treatment planning system and were transferred to an Elekta linac. During the beam delivery, dynamic machine parameters such as positions of the multi-leaf collimator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Standard deviation (SD) of the dGPR was calculated as a function of pGPR. 7)] for each tolerance. Red, blue, and green lines are data of the 3%/3-mm, 3%/2-mm, and 2%/2-mm tolerances.…”
Section: C Prediction Of Gamma Passing Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Standard deviation (SD) of the dGPR was calculated as a function of pGPR. 7)] for each tolerance. Red, blue, and green lines are data of the 3%/3-mm, 3%/2-mm, and 2%/2-mm tolerances.…”
Section: C Prediction Of Gamma Passing Ratementioning
confidence: 99%
“…Recently, a variety of attempts have been made to estimate the IM complexity and to investigate their relationship between the IM and gamma passing rate (GPR), which may potentially help to omit the patient-specific QA and to improve the efficiency of the clinical QA practice. A complexity metric (CM) that may be related to the GPR has been proposed by several authors, [3][4][5][6][7][8][9][10] resulting in limited predictability of the GPR. Deep learning (DL)-based prediction showed a good performance for the planar dose distribution measured using the film.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the correlation of the substitute with the gamma passing rate (GPR) is examined in order to maintain the criteria of current clinical QA practice. Complexity metrics of IMRT were proposed and investigated by several authors in recent years . The modulation complexity score (MCS) developed by McNiven et al .…”
Section: Introductionmentioning
confidence: 99%
“…The researchers investigated the correlation between the MCS and the delivered dose measured by a two‐dimensional (2D) diode array in terms of beam parameters such as the number of segments and monitor units (MUs). Other authors reported correlations between the MCS and GPR in volumetric‐modulated arc therapy (VMAT) . Although there are various other approaches, there is no satisfactory technique to substitute for the gamma analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation